Training regulations and how they come about - Kuppe, Anna Maria [Herausgeber]; Lorig, Barbara [Herausgeber]; Stöhr, Andreas [Herausgeber]; Schwarz, Henrik [Herausgeber] (Bundesinstitut für Berufsbildung, 2014)
"This brochure provides information on a unique procedure for the development of training regulations. The arrangements form the basis for initial training in dual system, in which many people in Germany begin their vocational qualification." This procedure involves those affected - employers organisations for the enterprises and trade unions for workers - in all important decisions about the content, objectives, duration and requirements of training. How does this procedure operate? Experts from training practice develop the outlines of the new training regulations together with the Federal Institute for Vocational Education and Training (BIBB) and harmonise them with experts from the vocational schools. Employers and trade unions promote the new training regulations in the enterprises and the Federal Government gives them the force of law." (BIBB-Doku)
Frühere Ausgaben u.d.T.: Vocational training regulations and the process behind them
Dt. Ausgabe u.d.T.: Ausbildungsordnungen und wie sie entstehen
Keywords: S 2.2.1 Ordnung von Ausbildungsberufen; S 3.5.2.2 Bundesinstitut für Berufsbildung (BIBB); Neuordnung der Ausbildungsberufe; Ausbildungsordnung; Verfahren